2022
DOI: 10.3390/nu14030558
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Bioactive Components in Quinoa (Chenopodium quinoa Willd.) Greens: A Review

Abstract: Quinoa (Chenopodium quinoa Willd.) is a nutrient-rich grain native to South America and eaten worldwide as a healthy food, sometimes even referred to as a ”superfood”. Like quinoa grains, quinoa greens (green leaves, sprouts, and microgreens) are also rich in nutrients and have health promoting properties such as being antimicrobial, anticancer, antidiabetic, antioxidant, antiobesity, and cardio-beneficial. Quinoa greens are gluten-free and provide an excellent source of protein, amino acids, essential mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 72 publications
5
64
1
8
Order By: Relevance
“…We evidenced that the combined application of Si(F + R) was associated with high content of phenolic compounds in leaves, in comparison to the treatments foliar application [Si(F)] and no Si application [Si(0)]. This information is relevant, since it was indicated that quinoa leaves can also be consumed as cooked vegetables and as a salad, increasing its interest as a functional food 24 . An increased production of phenolic compounds due to Si application has been reported in cucumber 25 and barley crops 19 .…”
Section: Resultsmentioning
confidence: 80%
“…We evidenced that the combined application of Si(F + R) was associated with high content of phenolic compounds in leaves, in comparison to the treatments foliar application [Si(F)] and no Si application [Si(0)]. This information is relevant, since it was indicated that quinoa leaves can also be consumed as cooked vegetables and as a salad, increasing its interest as a functional food 24 . An increased production of phenolic compounds due to Si application has been reported in cucumber 25 and barley crops 19 .…”
Section: Resultsmentioning
confidence: 80%
“…It is widely grown in Latin America, especially in South America, where it originated 5000 years ago near the current Peruvian-Bolivian border near Lake Titicaca (Estrella et al, 2018). Quinoa has a protein content of 9.1 to 15.7 %, carbohydrate content of 48.5 to 69.8%, fat content of 4.0 to7.6% and mineral content of 2.0 to 7.7% (Pathan et al, 2022).Quinoa has a rich bioactive profile, and it includes bioactive compounds like flavonoids (quercetin and kaempferol), phenolic acids (Ferulic, caffeic and p-coumaric), saponins, phytosterol (β-sitosterol, brassicasterol, campesterol, and stigmasterol), betalains (Betacyanins and Betaxan-thins), stilbenoids and tannins (Gallotannins, Ellagitannins, proanthocyanidins) (Hernández-Ledesma, 2019). These bioactive compounds have shown to exert biological activities such as anti-oxidant effect, Immunomodulatory effect, cardiovascular effect, anti-diabetic effect, antiobesity effect, neuroprotective effect and anti -hypertensive effect (Ng and Wang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, based on information on the presentation of exported products, published by Peru Trade Now (PROMPERU, 2020), round 91% in FOB value exported is in the form of grain, 3.6% in flakes, and 2.2% in flour [ 7 ]. Worldwide, quinoa cultivation has increased from 8 countries in 1980 to 100 by 2021 [ 8 ]. In this sense, the functional food market is constantly growing at a global level, which was estimated at US$ 162 billion in 2018 and was projected to reach US$ 280 billion by 2025, with an annual growth rate of around 8% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%